2015
DOI: 10.1007/s00253-015-7200-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid asymmetric reduction of ethyl 4-chloro-3-oxobutanoate using a thermostabilized mutant of ketoreductase ChKRED20

Abstract: Ethyl (S)-4-chloro-3-hydroxybutanoate ((S)-CHBE)is an important chiral intermediate for the synthesis of Bblockbuster^drug statins. The carbonyl reductase ChKRED20 from Chryseobacterium sp. CA49 was found to catalyze the bioreductive production of (S)-CHBE with excellent stereoselectivity (>99.5 % ee). Perceiving a capacity for improvement, we sought to increase the thermostability of Ch-KRED20 to allow a higher reaction temperature. After one round of error-prone PCR (epPCR) library screening followed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For the substrate COBE, we observed that the K m value of SmADH31 was only 0.42 mM, which was lower than that of other ADHs including ChADH (7.5 mM) and ScADH (0.59 mM). 21,22 The SmADH31 k cat /K m value for COBE was 5.5 × 10 2 mM −1 s −1 , which was higher than that of ChADH (26.8 mM −1 s −1 ) and ScADH (34.7 mM −1 s −1 ). All these results indicate that SmADH31 possesses a strong binding affinity and high catalytic efficiency for COBE.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…For the substrate COBE, we observed that the K m value of SmADH31 was only 0.42 mM, which was lower than that of other ADHs including ChADH (7.5 mM) and ScADH (0.59 mM). 21,22 The SmADH31 k cat /K m value for COBE was 5.5 × 10 2 mM −1 s −1 , which was higher than that of ChADH (26.8 mM −1 s −1 ) and ScADH (34.7 mM −1 s −1 ). All these results indicate that SmADH31 possesses a strong binding affinity and high catalytic efficiency for COBE.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…We selected the ketoreductase Ch KRED20 (cofactor NADH), with satisfactory ( R ) selectivity, 38 for screening reaction as a model enzyme. Given the optimized reaction conditions, we investigated the range and versatility of this method.…”
Section: Resultsmentioning
confidence: 99%
“…Enantiomerically pure alcohols are known as the important and valuable chiral synthons for the production of pharmaceutical and fine chemicals [39][40][41]. To investigate the substrate specificity of ChKRED12, some substrates (Table 2, 1a-7a, 10 mM) were tested.…”
Section: Substrate Specificity and Catalytic Propertiesmentioning
confidence: 99%